Laminar-Turbulent Transition 2000
DOI: 10.1007/978-3-662-03997-7_16
|View full text |Cite
|
Sign up to set email alerts
|

Receptivity for a Flat Plate with a Rounded Leading-Edge

Abstract: Abstract. The receptivity due to the interaction of an acoustic wave with a body which has a rounded leading edge and a region of low wall shear is considered. The body of interest is formed by a line source in a uniform stream. The nose radius, r * n , of this body is characterised in the theory through a parameter A = 2ω r * n /3U∞ where ω is the frequency of the acoustic wave and U∞ the mean flow speed. By comparing asymptotic and numerical results, the receptivity coefficient, C1, is calculated. The recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…It has also be shown that the first of the Lam-Rott eigenmodes matches to the unstable Tollmien-Schlichting (T-S) mode of the Orr-Sommerfeld equation, which exhibits exponential streamwise growth downstream (2). A similar asymptotic structure in the leading edge region has been shown to exist on both a parabolic body (16) and more general bodies where the slip velocity tends to a constant downstream (17). An equivalent asymptotic analysis in the Orr-Sommerfeld region for bodies other than the flat plate does not yet exist due to the complex structure in this region.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…It has also be shown that the first of the Lam-Rott eigenmodes matches to the unstable Tollmien-Schlichting (T-S) mode of the Orr-Sommerfeld equation, which exhibits exponential streamwise growth downstream (2). A similar asymptotic structure in the leading edge region has been shown to exist on both a parabolic body (16) and more general bodies where the slip velocity tends to a constant downstream (17). An equivalent asymptotic analysis in the Orr-Sommerfeld region for bodies other than the flat plate does not yet exist due to the complex structure in this region.…”
Section: Introductionmentioning
confidence: 77%
“…This boundary condition depends upon the form of the boundary layer at ξ 0 and the interaction of the free-stream disturbance with the boundary layer upstream of this point. This paper uses the boundary condition given by (30) which is the first Lam-Rott eigenmode of the asymptotic receptivity analysis in the vicinity of the leading edge (12,17,30). This mode is chosen because it is the only discrete eigenmode which exhibits streamwise growth after the lower branch neutral stability point and hence will dominate the solution far downstream.…”
Section: Formulation Of the Parabolized Stability Equation Schemementioning
confidence: 99%
See 2 more Smart Citations
“…The asymptotic Lam-Rott eigenmodes for a flat plate have been generalised for a parabolic body by Hammerton & Kerschen (1996), who also calculate the free-stream dependent receptivity coefficient as a function of the nose radius. This analysis has been generalised further by Nichols (2001) to bodies which have an inviscid free-stream velocity which tends to unity far downstream. Nichols also calculates the receptivity coefficient for the Rankine body as a function of the nose radius.…”
Section: Introductionmentioning
confidence: 99%